Perswazyjność operatorów modalności epistemicznej naprawdę i tak naprawdę w języku polityki na przykładzie wybranych programów publicystycznych Tomasz lis na żywo, Kropka nad i i Fakty po "Faktach" - Dupel, Magdalena (Słowo. Studia językoznawcze, 2013)
The paper presents the review of selected expressions of epistemic modality “naprawdę” (really) and “tak naprawdę” (at bottom) in the coaxing function specific for modern political language. When the politicians and the journalists comment on current foreign and national affairs, they want to convince the spectators, in consequence potential voters, to support the decisions made by the government or by the opposition. The stress put on the subjective attitude of a speaker toward the truth transferring in his message is one of the many possible methods of persuasion used in written texts by means of metatext expressions.